Preaching and popular Christianity: reading the sermons of John Chrysostom - Cook, James Daniel (Oxford theology and religion monographs, 2019)
This study reassess how we read Chrysostom's sermons, with a particular focus on the stern language which permeated his preaching, and on which the image of the contrary congregation is largely based. In doing this, it recovers a neglected portrayal of Chrysostom as a pastor and of preaching as a pastoral and liturgical activity